Unemployment among graduates in Kuching / Danillia Nuga, Noor Shaizahani Mohd Syahril and Nur Khairunissa Nawawi - Nuga, Danillia; Mohd. Syahril, Noor Shaizahani; Nawawi, Nur Khairunissa (2012)
This study was carried out to identify the most factors that cause the unemployment among graduates. The 100 respondents are comes from Kuching which are conducted by giving out the questionnaire to respondents which are different age, background and etc. A set of questionnaire was designed to gain primary data from the respondents about the causes of unemployment and how to solve the problem. The overall findings the causes such as graduates is too choosy, lack of experience and skills, lack of exposure, limited of vacancy and choosy employers and etc. In conclusions, some suggestion have been made to solve the problem of unemployment among graduates in Kuching, Sarawak and recommendation for future research has also been included in the final part of the report.